Penerapan Permainan Tradisional Pada Main Pembukaan Pembelajaran Anak Usia Dini - Dwi Istati Rahayu; Nurhasanah Nurhasanah; I Nyoman Suarta (Indonesian Publication Center, 2021)
Opening play is an important stage in early childhood learning, to stimulate children's gross motor skills. The research objective was to apply traditional games in playing openings to improve learning readiness in the classroom. This action research was conducted in two cycles, with each meeting four times at a kindergarten in the city of Mataram. Each cycle consists of planning, action, observation and evaluation, and reflection stages. The research subjects consisted of 16 children. The data obtained were analyzed using qualitative analysis. The traditional game applied in this research is Lung-lung Se from the Sasak tribe. The results showed that the children were happier than gymnastics and marching, interaction and cooperation between children had been established before entering the classroom so that when learning in the classroom the children were more focused on playing or learning activities. It can be concluded that learning in the classroom becomes more conducive after implementing traditional games in opening play activities.